Saccade direction encoding in the primate entorhinal cortex during visual exploration - Killian, Nathaniel J. (Proc Natl Acad Sci U S A, 2015)
We recently demonstrated that position in visual space is represented by grid cells in the primate entorhinal cortex (EC), suggesting that visual exploration of complex scenes in primates may employ signaling mechanisms similar to those used during exploration of physical space via movement in rodents. Here, we describe a group of saccade direction (SD) cells that encode eye movement information in the monkey EC during free-viewing of complex images. Significant saccade direction encoding was found in 20% of the cells recorded in the posterior EC. SD cells were generally broadly tuned and two largely separate populations of SD cells encoded future and previous saccade direction. Some properties of these cells resemble those of head-direction cells in rodent EC, suggesting that the same neural circuitry may be capable of performing homologous spatial computations under different exploratory contexts.